Amplify-forward and decode-forward: a novel power allocation technique for MIMO cognitive radio network - Monisha, M; Meena, M; Sharanya, C; Jaya, T (International Journal of Engineering and Technology, 2018)
Nowadays transmitting data through wireless communication channel requires more power than the wired communication channel. In other words any communication through wireless medium will consume more power. Since power is a limited source, it is hard to conserve it or reduce its usage and this leads to the concept of â€œEfficient power allocation scheme for MIMO (Multi Input Multi Output) cognitive radioâ€ system. The proposed system uses two algorithms namely On/Off Based Scheduling (OOBS) and Selective Based Scheduling (SBS) in Amplify and Forward (AAF) and Decode and Forward (DAF) techniques. OOBS algorithm is used for efficient allocation of the input power to each userâ€™s Signal to Noise Ratio (SNR) value. The proposed algorithm provides better power utilization with low bit error rate (9.53Ã—10-7).Â Â